Let a small bank fail: Implicit nonguarantee and financial contagion - Liyuan Liu; Xianshuang Wang; Zhen Zhou (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
This paper examines the consequences of Chinese regulators deviating from a long-standing full bailout policy in addressing the distress of a city-level commercial bank. This policy shift led to a persistent widening of credit spreads and a significant decline in funding ratios for negotiable certificates of deposit issued by small banks relative to large ones. Our empirical analysis reveals a novel contagion mechanism driven by reduced confidence in future bailouts (implicit non-guarantee), contributing to the subsequent collapse of other small banks. However, in the longer term, this policy shift improved price efficiency, credit allocation, and discouraged risk-taking among small banks.
urn:nbn:fi-fe2024101882357
Keywords: G14; G21; G28; H81; 330; Implicit guarantee; Bailout; Contagion; Price efficiency; Credit allocation; TBTF